The Relevance of and Surgical Approach to the Suprahyoid Region in Thyroglossal Duct Surgery. (15th July 2020) - Koempel, Jeffrey A.; Brooks, Jennifer; Snow, Mikel H.; Osterbauer, Beth; Garcia, Erick; Bawab, Ramzi; Shows, Jared; Parham, David
Abstract : Objectives: Persistent or recurrent disease following excision of a thyroglossal duct cyst/sinus (TGDC) is often found in the suprahyoid region. Cadaver dissections were performed to identify and name important surgical landmarks in the suprahyoid area; a histopathologic analysis of surgical specimens was completed to determine the incidence and extent of microscopic disease; and clinical outcomes were compared to determine the efficacy of a specific anatomic dissection. Study Design: Retrospective case series. Methods: Standardized dissections of four adult cadavers were performed. Consecutive surgical specimens were examined for evidence of microscopic TDGC disease in the suprahyoid region, measuring the greatest width and length of disease. A retrospective review of all consecutive TGDC procedures was completed. Results: The important surgical landmarks in the suprahyoid area were identified in all cadavers. Microscopic disease in the suprahyoid area was found in 79% (37 of 47) of surgical specimens. The mean greatest length and width of microscopic disease was 12.4 mm and 1.4 mm, respectively. Following identification of these landmarks, the incidence of recurrent or persistent disease decreased ( P = .02) from 5% (8 of 159) to 0% (0 of 112). Conclusion: The majority of pediatric patients with a TGDC will have microscopic disease in the suprahyoid area. The surgical landmark of the fascial plane between the geniohyoid and genioglossus muscles demarcates the anterior and lateral borders of resection in the suprahyoid area. This approach can be used as a reliable and easily reproducible technique in TGDC surgery to increase confidence of achieving complete removal of disease in the suprahyoid area, avoiding persistent or recurrent disease and a revision procedure. Level of Evidence: 4 Laryngoscope, 131:553–558, 2021